2019
DOI: 10.1177/1758573219869206
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone “Selfies”—A reliable and accurate tool for measuring elbow range of motion

Abstract: Background To determine if self-taken photographs (“selfies”), performed independently after instruction by video or illustrated handout, would be an accurate and reliable tool for capturing elbow range of motion in patients with elbow contractures. Methods Fifty patients presenting with elbow contractures participated in the study. After completion of the selfie, the senior author clinically measured flexion and extension with a goniometer. The angles from the photographs were measured and analyzed. Results T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This method for assessing elbow ROM has been validated and proved to be accurate and reliable. 6,18 ROM measurements during physical examination and photographs were rounded to the nearest 5° interval and then recorded. Additionally, patients who underwent revision surgery were included in the survival analysis, but their PROs were not included in the final analysis of clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…This method for assessing elbow ROM has been validated and proved to be accurate and reliable. 6,18 ROM measurements during physical examination and photographs were rounded to the nearest 5° interval and then recorded. Additionally, patients who underwent revision surgery were included in the survival analysis, but their PROs were not included in the final analysis of clinical outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, smartphone mirror "selfies" were also shown to have excellent validity and intra-rater reliability when compared to manual goniometry, but patients' ability to take a usable selfie was inversely correlated with age. 65 Several studies have shown that smartphone applications possess moderate-to-excellent inter-rater reliability, intra-rater reliability and validity when compared to visual estimation, manual goniometry and digital inclinometers for elbow flexion, extension, pronation and supination. 22,[66][67][68][69][70][71][72][73] Among the apps currently available for download are Angle Meter (Smart Tool Factory; Google Play), 22 Dr. Goniometer, 70 Goniometer Pro, 69,71 GetMyROM, 66 and Measure (Apple; AppStore).…”
Section: Rom Assessmentmentioning
confidence: 99%